1987
DOI: 10.1148/radiology.165.3.3685359
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondritis dissecans: analysis of mechanical stability with radiography, scintigraphy, and MR imaging.

Abstract: Twenty-one joints with stable (n = 9) or loose (n = 12) osteochondritis dissecans (OCD) lesions were examined in 15 subjects with plain radiography, three-phase bone scintigraphy, and magnetic resonance (MR) imaging. The lesion size and the thickness of the sclerotic margin as measured on plain radiographs were good parameters for predicting loosening. However, bone scintigraphy was more sensitive and specific in determining the mechanical stability of OCD lesions. MR imaging permitted direct visualization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
1
8

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(66 citation statements)
references
References 0 publications
0
57
1
8
Order By: Relevance
“…Cahill [2,16] noted that surgery is needed if there is failure of conservative treatment, and that lesion detachment at any time is an absolute indication for surgery. Studies documenting MRI prognostic features of JOCD have demonstrated that the signal intensity within the osteochondral fragment does not correspond with stability [5,6], nor does visible disruption of the subchondral plate, as most lesions also show this finding [6,17]. The most reliable, but infrequently seen, sign of an unstable OCD lesion is a fluid-filled gap in the articular surface with or without a displaced fragment free in the joint [5,6,17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cahill [2,16] noted that surgery is needed if there is failure of conservative treatment, and that lesion detachment at any time is an absolute indication for surgery. Studies documenting MRI prognostic features of JOCD have demonstrated that the signal intensity within the osteochondral fragment does not correspond with stability [5,6], nor does visible disruption of the subchondral plate, as most lesions also show this finding [6,17]. The most reliable, but infrequently seen, sign of an unstable OCD lesion is a fluid-filled gap in the articular surface with or without a displaced fragment free in the joint [5,6,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Radiographs may show the lesion but cannot determine stability. Although there are many papers related to the prognostic role of MRI in OCD [5,6,7,8,9,10], most have combined adult and juvenile disease. Furthermore, the natural history of JOCD on serial MRI, including healing, has not been fully determined.…”
Section: Introductionmentioning
confidence: 99%
“…Likely because of the relatively low reported prevalence of osteochondritis dissecans 25 , the current evidence in the literature is based on small sample sizes, often with locations of lesions such as elbow, ankle, and knee combined, for determining the diagnostic performance of MRI relative to arthroscopy in identifying osteochondritis dissecans lesions 24,26,27 . The limitation of most diagnostic studies that examine the validity of screening tools such as MRI and that use arthroscopy as a gold standard comparison is that not all patients identified as having a potential osteochondritis dissecans lesion have an arthroscopic evaluation.…”
Section: Methodological Quality Of the Studiesmentioning
confidence: 99%
“…One of the most important determinations to be made prior to surgical intervention is the stability of the OCD lesion. The stability relates to the mechanical integrity of the subchondral lesion [43]. A lesion which is immobile and resting in situ is considered to be stable, whereas a lesion which is mobile, fragmented, or ex situ is considered unstable.…”
Section: Operative Treatmentmentioning
confidence: 99%